AN ANALYSIS OF USING CODE MIXING ON CINTA LAURA IN HOTMAN PARIS SHOW - Bahrudin, Dinar Vincy Yunitaka; Rohaniyah, Jaftiyatur; Setiyawan, Arisandi (The Ellite of Unira, 2024)
Nowdays, people speak more than one language as multilingual or bilingual. Mostly, Indonesian people usually use Indonesian and English to speak with others in their daily life. This research deals with a study of code mixing used by Cinta Laura Kiehl in Hotman Paris Show. The research problem are how code mixing used by Cinta Laura Kiehl in Hotman Paris Show and what types of code mixing used by Cinta Laura Kiehl in Hotman Paris Show . The objective of this study are to know the code mixing and the types of code mixing used by Cinta Laura Kiehl in Hotman Paris Show. This research use descriptive qualitative method. There are some ways to collect the data. The data collection used are audiovisual materials and documents. The data were collected then analyzed through organizing data, transcribing data and analyzing by hand. This research was found that there are two types of code mixing used by Cinta Laura Kiehl in Hotman Paris Show those are: Insertion code mixing and alternation code mixing. But, the dominant code mixing used is insertion code mixing. Then, the researcher conclude that the data discovered there are 92 data of code mixing. It can be inferred that the highest number of code mixing was insertion which attain 51 data. Meanwhile, code mixing of alternation are 41 data